Era pra ser, mas não foi - Cattaneo, Guilherme Hammel [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Between January and July 2019, I got an exchange scholarship at KOÇ University in Sar yer, İstanbul. An opportunity full of expectations and possibilities with the study of photography, cinema, culture and art in general. However, my expectations were proved far from reality: long study sessions competed with the time I had to explore and produce art. I would have never imagined that everything would only get worse between 2020 and 2022. With frustrated plans and unreachable goals, I ended up meeting Turkey’s own anxieties: Stories and places that reflected a future that never happened. Everything that was meant to be, but wasn’t. Increasingly burdened with contexts and difficulties, I intend to present in this work the aesthetic experiences that populate my photographs.

Entre janeiro e julho de 2019, consegui uma bolsa de intercâmbio na universidade de KOÇ, em Sarıyer, İstanbul. Uma oportunidade cheia de expectativas e possibilidades ao estudar fotografia, cinema, cultura e arte em geral. Contudo, minhas expectativas se mostraram longe da realidade: longas jornadas de estudo competiam com o tempo que tinha para explorar e produzir arte. Nunca imaginaria que tudo só pioraria entre 2020 e 2022. Em planos frustrados e expectativas inalcançáveis, acabei encontrando as ansiedades da própria Turquia; histórias e lugares que refletiam um futuro que nunca existiu: tudo aquilo que era para ser, mas não foi. Cada vez mais carregado de contextos e dificuldades, pretendo neste trabalho expor as experiências estéticas que povoam minhas fotografias.
That was meant to be, but wasn’t
Keywords: Art; Culture; Photography; Exchange; Arte; Cultura; Fotografia; Intercâmbio; Livro de fotografias; Turquia; Photobook; Turkey